Complexities during transitions to adulthood for youth with disabilities: person–environment interactions. (November 2014) - Stewart, Debra; Law, Mary; Young, Nancy L.; Forhan, Mary; Healy, Helen; Burke-Gaffney, Jan; Freeman, Matthew
Abstract Purpose: The purpose of this qualitative study was to explore the experiences of youth with different disabilities from across Canada during their transitions from adolescence to adulthood. Methods: Qualitative methods, using a phenomenological tradition, explored the meaning of the lived experiences of youth with disabilities in transition to adulthood. Purposeful sampling was used to select people with a range of experiences, background, location and demographic characteristics. Individual interviews with key informants and a focus group with an "expert panel" of participants were the methods of data collection. Data analysis was iterative and followed established practices of phenomenology. Results: Over 50 people, including youth with different disabilities, parents/caregivers and service providers from different organizations and systems across Canada participated in individual and/or focus group interviews. An overarching theme of "complexities" emerged from the data analysis. Complexities were related to the interactions between person and environment during transition experiences. Six subthemes about complexities were explored in depth to describe the primary person–environment interactions that were identified by study participants. Conclusions: The complexities involved in the interactions between person and environment during transitions to adulthood appear to be similar for youth with different types of disabilities. Recommendations are provided to address these complexities using holistic and collaborative approaches in service delivery and future research. Implications for Rehabilitation The complexities involved in transitions to adulthood appear to be similar for youth with different types of disabilities. Rehabilitation service providers can address these complexities using holistic, strengths-based and collaborative approaches. Service providers and researchers in rehabilitation need to acknowledge the interactions between person and environment rather than addressing each component separately. Future research should include youth, families and community members on research teams to ensure that complexities are adequately addressed.